Eksplorasi Nilai Nilai Stoikisme Dalam Sudut Pandang Islam - hilalludin, hilalludin; Januardi, Haris; Jumadi, Jumadi (UPT Publikasi Ilmiah, 2024)
Stoic philosophy has long been a foundation for moral and ethical life in Western civilization. On the other hand, Islam provides a comprehensive moral and spiritual guide. This research aims to explore how the core principles of Stoicism, such as self-control, courage, wisdom, and justice, share similarities with Islamic teachings. Through a comparative approach, this journal examines the parallels and distinctions between these two perspectives, and how Stoicism can be understood within the framework of Islamic teachings.